Alloy for samarium cobalt permanent magnet, alloy material, permanent magnet and preparation method and application
By adjusting the composition of the alloy for samarium-cobalt permanent magnets and forming a specific phase combination, the problem of difficult to improve the residual magnetism and coercivity of the existing SmCo5 permanent magnets is solved, and higher magnetic energy generation and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202111424595.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-26
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-11-26
AI Technical Summary
The residual magnetic and coercive forces of the existing SmCo5 permanent magnets are difficult to improve, the maximum magnetic energy accumulation is low, and the corrosion resistance is insufficient.
By adjusting the composition of the alloy for samarium-cobalt permanent magnets, including adding a specific proportion of rare earth elements (such as Sm, Pr, Y), iron (Fe), tin (Sn), aluminum (Al) and copper (Cu) to the alloy for samarium-cobalt permanent magnets, to optimize the microstructure of the alloy.
The residual magnetism, maximum magnetic energy product and intrinsic coercive force of samarium-cobalt permanent magnet are significantly improved, and the corrosion resistance of the material is enhanced.
Smart Images

Figure CN114284015B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a samarium-cobalt permanent magnet alloy, alloy material, permanent magnet, preparation method, and application. Background Technology
[0002] SmCo5, as a first-generation permanent magnet material, is widely used due to its high Curie temperature, high coercivity, and high saturation magnetization. The characteristics of SmCo5 permanent magnet alloys are: high magnetocrystalline anisotropy (K1 = (15~19)*10). 3 kJ / m 3 K1 is the magnetocrystalline anisotropy constant), high anisotropic field (HA = 31840 kA / m), low temperature coefficient (compared to rare earth iron-based permanent magnet alloys), and high Curie point (Tc = 720℃, Tc is the Curie point or Curie temperature, and the Tc of SmCo5 is more than twice as high as that of NdFeB).
[0003] SmCo5 permanent magnet alloys are generally used in precision instruments and microwave devices, such as traveling wave tubes, gyroscopes in aerospace systems, magnetic thrust bearings, as well as components with high dimensional accuracy requirements such as watch cores, sensors, and small motors. They play an irreplaceable role in high-temperature applications.
[0004] With the advancement of technology, the requirements for magnets in various fields are becoming increasingly stringent, primarily in terms of magnetic properties. Remanence and coercivity determine the strength of a magnet's "function." The theoretical maximum energy product (BH)max of SmCo5 is 244.9 kJ / m². 3 (31MGOe), but the actual maximum magnetic energy product is much lower than the theoretical one, which limits the application of SmCo5 materials. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to overcome the defects of existing SmCo5 permanent magnets, such as the inability to further improve remanence and coercivity, low maximum energy product and need to reduce corrosion resistance, and to provide an alloy for samarium cobalt permanent magnets, alloy materials, permanent magnets, preparation methods and applications.
[0006] The present invention solves the above-mentioned technical problems through the following solutions:
[0007] An alloy for samarium-cobalt permanent magnets comprises, by weight percentage, the following components:
[0008] R: 34.5–38 mas%, where R is a rare earth element and includes Sm;
[0009] Fe: 0.2–1 mas%;
[0010] M: 0.2–1 mas%, wherein M includes one or more of Sn, Al, Cu, Ga, and Zn;
[0011] Co: 60-65mas%, mas% refers to the mass percentage of each element in the alloy used for samarium-cobalt permanent magnets.
[0012] In this invention, the content of R is preferably in the range of 34.5 to 37.5 mas%, for example 35 mas%, 36.5 mas%, 35.5 mas%, or 36 mas%, where mas% refers to the mass percentage of each element in the alloy for samarium cobalt permanent magnets.
[0013] In this invention, R may also include one or more of Pr, Nd, Gd and Y, preferably including Pr and / or Y.
[0014] Wherein, when R also includes Pr, the content of Pr is preferably in the range of 0 to 15 mas%, and not 0, for example 5 mas%, mas% refers to the mass percentage of each element in the alloy for samarium cobalt permanent magnets.
[0015] When R further includes Y, the content of Y is preferably in the range of 0 to 18 mas%, and is not 0, for example 5 mas%. mas% refers to the mass percentage of each element in the alloy used for samarium-cobalt permanent magnets.
[0016] In this invention, the content of Sm is preferably in the range of 15 to 38 mas%, for example 34.5 mas%, 35 mas%, 36.5 mas%, 37.5 mas%, 20.5 mas%, 18 mas%, or 25 mas, where mas% refers to the mass percentage of each element in the alloy used for samarium-cobalt permanent magnets.
[0017] In this invention, the Fe content is preferably in the range of 0.3 to 1 mas%, for example 0.6 mas%, 0.5 mas%, or 0.8 mas%, where mas% refers to the mass percentage of each element in the alloy used for samarium-cobalt permanent magnets.
[0018] In this invention, the content of M is preferably in the range of 0.5 to 1 mas%, for example 0.55 mas% or 0.6 mas%, where mas% refers to the mass percentage of each element in the alloy for samarium cobalt permanent magnets.
[0019] In this invention, preferably, M includes one or more of Sn, Al, and Cu.
[0020] Wherein, when M includes Sn, the Sn content is preferably in the range of 0.3 to 1 mas%, for example 0.6 mas%, 0.4 mas%, or 0.5 mas%, where mas% refers to the mass percentage of each element in the alloy for samarium-cobalt permanent magnets.
[0021] Wherein, when M includes Al, the content of Al is preferably in the range of 0.1 to 0.5 mas%, for example 0.3 mas%, where mas% refers to the mass percentage of each element in the alloy for samarium-cobalt permanent magnets.
[0022] When M includes Cu, the Cu content is preferably in the range of 0.1 to 0.5 mas%, for example 0.15 mas%, where mas% refers to the mass percentage of each element in the alloy for samarium-cobalt permanent magnets.
[0023] In this invention, the Co content is preferably in the range of 60 to 64.5 mas%, for example 64.3 mas%, 63.8 mas%, 62.4 mas%, 61.65 mas%, 61.2 mas%, 62.9 mas%, 62.6 mas%, or 63.8 mas%, where mas% refers to the mass percentage of each element in the samarium-cobalt permanent magnet alloy.
[0024] In this invention, the samarium-cobalt permanent magnet alloy preferably comprises the following components by weight percentage:
[0025] Sm, 15~38mas%; Co, 60~64.5mas%; Fe, 0.3~1mas%; Sn, 0.3~1mas%.
[0026] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy is preferably composed of the following components by weight percentage:
[0027] Sm, 35mas%; Co, 63.8mas%; Fe, 0.6mas%; Sn, 0.6mas%.
[0028] In this invention, the samarium-cobalt permanent magnet alloy preferably comprises the following components by weight percentage:
[0029] Sm, 15~38mas%; Co, 60~64.5mas%; Fe, 0.3~1mas%; Sn, 0.3~1mas%, Al, 0.1~0.5mas%.
[0030] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy is preferably composed of the following components by weight percentage:
[0031] Sm, 34.5mas%; Co, 64.3mas%; Fe, 0.6mas%; Sn, 0.3mas%, Al, 0.3mas%.
[0032] In this invention, the samarium-cobalt permanent magnet alloy preferably comprises the following components by weight percentage:
[0033] Sm, 15~38mas%; Co, 60~64.5mas%; Fe, 0.3~1mas%; Sn, 0.3~1mas%, Al, 0.1~0.5mas%, Cu0.1~0.5mas%.
[0034] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy is preferably composed of the following components by weight percentage:
[0035] Sm, 36.5mas%; Co, 62.4mas%; Fe, 0.5mas%; Sn, 0.4mas%, Al, 0.1mas%, Cu0.1mas%.
[0036] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy is preferably composed of the following components by weight percentage:
[0037] Sm, 37.5mas%; Co, 61.65mas%; Fe, 0.3mas%; Sn, 0.3mas%, Al, 0.1mas%, Cu0.15mas%.
[0038] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy is preferably composed of the following components by weight percentage:
[0039] Sm, 38mas%; Co, 61.2mas%; Fe, 0.2mas%; Sn, 0.5mas%, Cu0.1mas%.
[0040] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy is preferably composed of the following components by weight percentage:
[0041] Sm, 20.5mas%; Pr, 15mas%; Co, 62.9mas%; Fe, 1mas%; Sn, 0.6mas%.
[0042] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy is preferably composed of the following components by weight percentage:
[0043] Sm, 18mas%; Y, 18mas%; Co, 62.6mas%; Fe, 0.8mas%; Sn, 0.5mas%; Al0.1mas%.
[0044] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy is preferably composed of the following components by weight percentage:
[0045] Sm, 25mas%; Pr5mas%; Y, 5mas%; Co, 63.8mas%; Fe, 0.6mas%; Sn, 0.6mas%.
[0046] The present invention also provides an alloy material for samarium-cobalt permanent magnets, which comprises the following components by mass percentage:
[0047] R: 34.5–38 mas%, where R is a rare earth element and includes Sm;
[0048] Fe: 0.2–1 mas%;
[0049] M: 0.2–1 mas%, wherein M includes one or more of Sn, Al, Cu, Ga, and Zn;
[0050] Co: 60-65 mas%; mas% refers to the mass percentage of each element in the alloy material used for samarium-cobalt permanent magnets;
[0051] The alloy material for the samarium cobalt permanent magnet comprises an RCO5 phase, an R2CO7 phase, and a grain boundary phase, and the sum of the volume ratios of the RCO5 phase, the R2CO7 phase, and the grain boundary phase is 100%; the RCO5 phase comprises an SmCo5 phase, and the R2CO7 phase comprises an Sm2Co7 phase.
[0052] In this invention, the volume of the RCO5 phase is preferably 55% to 85%, for example 78.8%, 72.5%, 64.7%, 60.2%, 56.3%, 71.1%, 68.4%, or 70.8%.
[0053] In this invention, the volume of the R2CO7 phase is preferably 15% to 45%, for example 18.1%, 24.5%, 32.5%, 37.9%, 42.0%, 24.8%, 28.0%, or 26.0%.
[0054] In this invention, the volume of the grain boundary phase is preferably 1% to 5%, for example 3.1%, 3.0%, 2.8%, 2.0%, 1.7%, 4.1%, 3.6%, or 3.2%.
[0055] In this invention, the grain boundary phase may be a CoSn phase and / or a CoSn2 phase.
[0056] In this invention, the content of R is preferably in the range of 34.54 to 37.89 mas%, for example 35.05 mas%, 36.53 mas%, 37.48 mas%, 35.57 mas%, 36.11 mas%, or 35.13 mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets.
[0057] In this invention, R may also include one or more of Pr, Nd, Gd and Y, preferably including Pr and / or Y.
[0058] Preferably, the RCO5 phase also includes the YCo5 phase and / or the PrCO5 phase.
[0059] Preferably, the R2CO7 phase also includes the Y2Co7 phase and / or the Pr2CO7 phase.
[0060] Wherein, when R also includes Pr, the content of Pr is preferably in the range of 0 to 15.5 mas%, and not 0, for example 5.04 mas% or 15.01 mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets.
[0061] Wherein, when R also includes Y, the content of Y is preferably in the range of 0 to 18 mas%, and not 0, for example 4.97 mas% or 17.96 mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets.
[0062] In this invention, the Sm content is preferably in the range of 15mas% to 38mas%, for example 34.54mas%, 35.05mas%, 36.53mas%, 37.48mas%, 37.89mas%, 20.56mas%, 18.15mas%, or 25.12mas, where mas% refers to the mass percentage of each element in the alloy material for samarium-cobalt permanent magnets.
[0063] In this invention, the Fe content is preferably in the range of 0.21 mas% to 1 mas%, for example 0.61 mas%, 0.62 mas%, 0.53 mas%, 0.32 mas%, 0.95 mas%, 0.77 mas% or 0.64 mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets.
[0064] In this invention, the content of M is preferably in the range of 0.5 to 1 mas%, for example 0.55 mas% or 0.6 mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets.
[0065] In this invention, preferably, M includes one or more of Sn, Al, and Cu.
[0066] Wherein, when M includes Sn, the Sn content is preferably in the range of 0.3 to 1 mas%, for example 0.31 mas%, 0.58 mas%, 0.44 mas%, 0.32 mas%, 0.51 mas%, 0.62 mas%, 0.54 mas%, or 0.64 mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets.
[0067] Wherein, when M includes Al, the content of Al is preferably in the range of 0.1 to 0.5 mas%, for example 0.12 mas% or 0.32 mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium-cobalt permanent magnets.
[0068] When M includes Cu, the content of Cu is preferably in the range of 0.1 to 0.5 mas%, for example, 0.15 mas%, 0.11 mas%, or 0.13 mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium-cobalt permanent magnets.
[0069] In this invention, the Co content is preferably in the range of 60 to 64.5 mas%, for example 64.22 mas%, 63.75 mas%, 62.27 mas%, 61.63 mas%, 61.28 mas%, 62.86 mas%, 62.48 mas%, or 63.59 mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium-cobalt permanent magnets.
[0070] In this invention, the samarium-cobalt permanent magnet alloy material is preferably composed of the following components by weight percentage:
[0071] Sm, 15–38 mas%; Co, 60–64.5 mas%; Fe, 0.3–1 mas%; Sn, 0.3–1 mas%; RCO5 phase 55%–85%, R2Co7 phase 15%–45%, grain boundary phase 1%–5%.
[0072] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy material is preferably composed of the following components by weight percentage:
[0073] Sm, 35.05 mas%; Co, 63.75 mas%; Fe, 0.62 mas%; Sn, 0.58 mas%, SmCo5 phase 72.5%, Sm2Co7 phase 24.5%, grain boundary phase 3%.
[0074] In this invention, the samarium-cobalt permanent magnet alloy material is preferably composed of the following components by weight percentage:
[0075] Sm, 15–38 mas%; Co, 60–64.5 mas%; Fe, 0.3–1 mas%; Sn, 0.3–1 mas%; Al, 0.1–0.5 mas%; RCO5 phase 55%–85%, R2Co7 phase 15%–45%, grain boundary phase 1%–5%.
[0076] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy material is preferably composed of the following components by weight percentage:
[0077] Sm, 34.54 mas%; Co, 64.22 mas%; Fe, 0.61 mas%; Sn, 0.31 mas%; Al, 0.32 mas%; SmCo5 phase 78.8%, Sm2Co7 phase 18.1%, grain boundary phase 3.1%.
[0078] In this invention, the samarium-cobalt permanent magnet alloy material is preferably composed of the following components by weight percentage:
[0079] Sm, 15–38 mas%; Co, 60–64.5 mas%; Fe, 0.3–1 mas%; Sn, 0.3–1 mas%; Al, 0.1–0.5 mas%; Cu, 0.1–0.5 mas%; RCO5 phase 55%–85%; R2Co7 phase 15%–45%; grain boundary phase 1%–5%.
[0080] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy material is preferably composed of the following components by weight percentage:
[0081] Sm, 36.53 mas%; Co, 62.27 mas%; Fe, 0.53 mas%; Sn, 0.44 mas%; Al, 0.12 mas%; Cu, 0.11 mas%; SmCo5 phase 64.7%; Sm2Co7 phase 32.5%; grain boundary phase 2.8%.
[0082] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy material is preferably composed of the following components by weight percentage:
[0083] Sm, 37.48 mas%; Co, 61.63 mas%; Fe, 0.32 mas%; Sn, 0.32 mas%; Al, 0.1 mas%; Cu, 0.15 mas%; SmCo5 phase 60.2%; Sm2Co7 phase 37.9%; grain boundary phase 2%.
[0084] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy material is preferably composed of the following components by weight percentage:
[0085] Sm, 37.89 mas%; Co, 61.28 mas%; Fe, 0.21 mas%; Sn, 0.49 mas%; Cu, 0.13 mas%; SmCo5 phase, 56.3%; Sm2Co7 phase, 42%; grain boundary phase, 1.7%.
[0086] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy material is preferably composed of the following components by weight percentage:
[0087] Sm, 20.56 mas%; Pr, 15.01 mas%; Co, 62.86 mas%; Fe, 0.95 mas%; Sn, 0.62 mas%, SmCo5 and PrCO5 phases 71.1%, Sm2Co7 and Pr2CO7 phases 24.8%, grain boundary phases 4.1%.
[0088] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy material is preferably composed of the following components by weight percentage:
[0089] Sm, 18.15 mas%; Y, 17.96 mas%; Co, 62.48 mas%; Fe, 0.77 mas%; Sn, 0.54 mas%; Al 0.1 mas%, SmCo5 and YCo5 phases 68.4%, Sm2Co7 and Y2Co7 phases 28%, grain boundary phases 3.6%.
[0090] In a preferred embodiment of the present invention, the samarium-cobalt permanent magnet alloy material is preferably composed of the following components by weight percentage:
[0091] Sm, 25.12 mas%; Pr, 5.04 mas%; Y, 4.97 mas%; Co, 63.59 mas%; Fe, 0.64 mas%; Sn, 0.64 mas%, SmCo5, PrCO5 and YCo5 phases 70.8%, Sm2Co7, Pr2CO7 and Y2Co7 phases 26%, grain boundary phases 3.2%.
[0092] In this invention, the differences in the composition and content of the various components in the samarium cobalt permanent magnet alloy and the samarium cobalt permanent magnet alloy material are due to the volatilization of elements during the smelting process, fluctuations in the testing system, etc. When the content of some elements decreases, the relative proportion of other elements will increase. Generally, the acceptable error range for the fluctuation of the main element composition (e.g., elements with a content of more than 2 mas%) is within ±2%, and the fluctuation range for minor elements (<2 mas%) is within ±10%.
[0093] The present invention also provides a method for preparing an alloy material for samarium cobalt permanent magnets, which includes the following steps: melting and casting the above-mentioned alloy for samarium cobalt permanent magnets.
[0094] In this invention, the smelting is generally carried out in a vacuum smelting furnace.
[0095] In this invention, the melting time can be 1 to 5 hours, for example, 70 minutes.
[0096] In this invention, the melting temperature can be 1480-1580℃.
[0097] In this invention, the pressure during the smelting process can be 50-80 kPa.
[0098] In this invention, the casting method can be conventional in the art, such as the strip casting method, centrifugal casting method, or BOOKMOLD type casting method.
[0099] The present invention also provides a samarium cobalt permanent magnet, which comprises the following components by mass percentage:
[0100] R: 34.5–35.5 mas%, where R is a rare earth element and contains Sm;
[0101] Fe: 0.2–1 mas%;
[0102] M: 0.2–1 mas%, wherein M includes one or more of Sn, Al, Cu, Ga, and Zn;
[0103] Co: 60-65 mas%;
[0104] The samarium cobalt permanent magnet comprises RCO5 phase, R2CO7 phase and grain boundary phase;
[0105] The volume percentage of the RCO5 phase is more than 85% and not more than 100%.
[0106] The volume percentage of the R2CO7 phase is 0-15%;
[0107] The volume percentage of the grain boundary phase is 1-3%, and the sum of the volume ratios of the RCO5 phase, the R2CO7 phase, and the grain boundary phase is 100%.
[0108] The RCO5 phase contains the SmCo5 phase, and the R2CO7 phase contains the Sm2Co7 phase;
[0109] mas% refers to the percentage of each element in the mass of a samarium-cobalt permanent magnet.
[0110] In this invention, the volume of the RCO5 phase is preferably 85% to 95%, for example 92.8%, 92.2%, 91.1%, 88.7%, 86.5%, 91.8%, 91.5%, or 92%.
[0111] In this invention, the volume fraction of the R2CO7 phase is preferably 5-13%, for example 5.4%, 6.3%, 7.5%, 10.1%, 12.3%, 5.8%, 6.4%, or 6.3%.
[0112] In this invention, the volume of the grain boundary phase is preferably 1 to 2.5%, for example 1.8%, 1.5%, 1.4%, 1.2%, 2.4%, 2.1%, or 1.7%.
[0113] In this invention, the grain boundary phase may be one or more of CoSn, CoSn2 phase and Sm2O3.
[0114] In this invention, the content of R is preferably in the range of 34.5 to 35.5 mas%, for example 34.81 mas%, 34.92 mas%, 34.83 mas%, 35.07 mas%, 35.31 mas%, 35.43 mas%, 35.01 mas%, or 34.93 mas%, where mas% refers to the mass percentage of each element in the samarium cobalt permanent magnet.
[0115] In this invention, R may also include one or more of Pr, Nd, Gd and Y, preferably including Pr and / or Y.
[0116] Preferably, the RCO5 phase also includes the YCo5 phase and / or the PrCO5 phase.
[0117] Preferably, the R2CO7 phase also includes the Y2Co7 phase and / or the Pr2CO7 phase.
[0118] Wherein, when R also includes Pr, the content of Pr is preferably in the range of 0 to 15.5 mas%, and not 0, for example 5.1 mas% or 15.21 mas%, where mas% refers to the mass percentage of each element in the samarium cobalt permanent magnet.
[0119] Wherein, when R also includes Y, the content of Y is preferably in the range of 0 to 18 mas%, and not 0, for example 4.92 mas% or 17.38 mas%, where mas% refers to the mass percentage of each element in the samarium cobalt permanent magnet.
[0120] In this invention, the content of Sm is preferably in the range of 15mas% to 35.5mas%, for example 34.81mas%, 34.92mas%, 34.83mas%, 35.07mas%, 35.31mas%, 20.22mas%, 17.63mas%, or 24.91mas, where mas% refers to the mass percentage of each element in the samarium cobalt permanent magnet.
[0121] In this invention, the Fe content is preferably in the range of 0.21 mas% to 1 mas%, for example 0.54 mas%, 0.56 mas%, 0.45 mas%, 0.28 mas%, 0.89 mas%, 0.73 mas% or 0.61 mas%, where mas% refers to the mass percentage of each element in the samarium cobalt permanent magnet.
[0122] In this invention, the content of M is preferably in the range of 0.4 to 1 mas%, for example 0.61 mas%, 0.55 mas%, 0.71 mas%, 0.67 mas%, 0.61 mas%, 0.43 mas%, 0.7 mas%, or 0.57 mas, where mas% refers to the mass percentage of each element in the samarium cobalt permanent magnet.
[0123] In this invention, preferably, M includes one or more of Sn, Al, and Cu.
[0124] Wherein, when M includes Sn, the Sn content range is preferably 0.25 to 1 mas%, for example 0.28 mas%, 0.55 mas%, 0.36 mas%, 0.33 mas%, 0.46 mas%, 0.43 mas%, 0.51 mas%, or 0.57 mas%, where mas% refers to the mass percentage of each element in the samarium cobalt permanent magnet.
[0125] When M includes Al, the content of Al is preferably in the range of 0.1 to 0.5 mas%, for example 0.33 mas%, 0.22 mas%, 0.21 mas%, or 0.19 mas%, where mas% refers to the mass percentage of each element in the samarium cobalt permanent magnet.
[0126] Wherein, when M includes Cu, the content of Cu is preferably in the range of 0.1 to 0.5 mas%, for example 0.15 mas% or 0.13 mas%, where mas% refers to the mass percentage of each element in the samarium cobalt permanent magnet.
[0127] In this invention, the Co content is preferably in the range of 60 to 64.5 mas%, for example 64.04 mas%, 63.97 mas%, 64.01 mas%, 63.98 mas%, 63.9 mas%, 63.25 mas%, 63.56 mas%, or 63.89 mas%, where mas% refers to the mass percentage of each element in the samarium cobalt permanent magnet.
[0128] In this invention, the samarium cobalt permanent magnet is preferably composed of the following components by weight percentage:
[0129] Sm, 15 mas%–35.5 mas%; Co, 60–64.5 mas%; Fe, 0.3–1 mas%; Sn, 0.25–1 mas%; RCO5 phase 85%–95%, R2Co7 phase 5–13%, grain boundary phase 1–2.5%.
[0130] In a preferred embodiment of the present invention, the samarium cobalt permanent magnet is preferably composed of the following components by weight percentage:
[0131] Sm, 34.92 mas%; Co, 63.97 mas%; Fe, 0.56 mas%; Sn, 0.55 mas%, SmCo5 phase 92.2%, Sm2Co7 phase 6.3%, grain boundary phase 1.5%.
[0132] In this invention, the samarium cobalt permanent magnet is preferably composed of the following components by weight percentage:
[0133] Sm, 15 mas%–35.5 mas%; Co, 60–64.5 mas%; Fe, 0.3–1 mas%; Sn, 0.25–1 mas%; Al, 0.1–0.5 mas%; RCO5 phase 85%–95%, R2Co7 phase 5–13%, grain boundary phase 1–2.5%.
[0134] In a preferred embodiment of the present invention, the samarium cobalt permanent magnet is preferably composed of the following components by weight percentage:
[0135] Sm, 34.81 mas%; Co, 64.04 mas%; Fe, 0.54 mas%; Sn, 0.28 mas%; Al, 0.33 mas%; SmCo5 phase 92.8%, Sm2Co7 phase 5.4%, grain boundary phase 1.8%.
[0136] In this invention, the samarium cobalt permanent magnet is preferably composed of the following components by weight percentage:
[0137] Sm, 15 mas%–35.5 mas%; Co, 60–64.5 mas%; Fe, 0.3–1 mas%; Sn, 0.25–1 mas%; Al, 0.1–0.5 mas%; Cu, 0.1–0.5 mas%; RCO5 phase 85%–95%; R2Co7 phase 5%–13%; grain boundary phase 1%–2.5%.
[0138] In a preferred embodiment of the present invention, the samarium cobalt permanent magnet is preferably composed of the following components by weight percentage:
[0139] Sm, 34.83 mas%; Co, 64.01 mas%; Fe, 0.45 mas%; Sn, 0.36 mas%; Al, 0.22 mas%; Cu, 0.13 mas%; SmCo5 phase 91.1%; Sm2Co7 phase 7.5%; grain boundary phase 1.4%.
[0140] In a preferred embodiment of the present invention, the samarium cobalt permanent magnet is preferably composed of the following components by weight percentage:
[0141] Sm, 35.07 mas%; Co, 63.98 mas%; Fe, 0.28 mas%; Sn, 0.33 mas%; Al, 0.21 mas%; Cu, 0.13 mas%; SmCo5 phase 88.7%; Sm2Co7 phase 10.1%; grain boundary phase 1.2%.
[0142] In a preferred embodiment of the present invention, the samarium cobalt permanent magnet is preferably composed of the following components by weight percentage:
[0143] Sm, 35.31 mas%; Co, 63.9 mas%; Fe, 0.21 mas%; Sn, 0.43 mas%; Cu, 0.15 mas%; SmCo5 phase, 86.5%; Sm2Co7 phase, 12.3%; grain boundary phase, 1.2%.
[0144] In a preferred embodiment of the present invention, the samarium cobalt permanent magnet is preferably composed of the following components by weight percentage:
[0145] Sm, 20.22 mas%; Pr, 15.21 mas%; Co, 63.25 mas%; Fe, 0.89 mas%; Sn, 0.43 mas%, SmCo5 and PrCO5 phases 91.8%, Sm2Co7 and Pr2CO7 phases 5.8%, grain boundary phases 2.4%.
[0146] In a preferred embodiment of the present invention, the samarium cobalt permanent magnet is preferably composed of the following components by weight percentage:
[0147] Sm, 17.63 mas%; Y, 17.38 mas%; Co, 63.56 mas%; Fe, 0.73 mas%; Sn, 0.49 mas%; Al 0.19 mas%, SmCo5 and YCo5 phases 91.5%, Sm2Co7 and Y2Co7 phases 6.4%, grain boundary phases 2.1%.
[0148] In a preferred embodiment of the present invention, the samarium cobalt permanent magnet is preferably composed of the following components by weight percentage:
[0149] Sm, 24.91 mas%; Pr, 5.1 mas%; Y, 4.92 mas%; Co, 63.89 mas%; Fe, 0.61 mas%; Sn, 0.57 mas%, SmCo5, PrCO5 and YCo5 phases 92%, Sm2Co7, Pr2CO7 and Y2Co7 phases 6.3%, grain boundary phases 1.7%.
[0150] In this invention, the differences in the alloy material used for the samarium-cobalt permanent magnet and the various components and contents in the samarium-cobalt permanent magnet are due to the removal of some fine powder in the embodiments. The removed fine powder mainly contains the R2CO7 phase, which is rich in Sm compared to the RCO5 phase. Therefore, the removal of powder containing the R2CO7 phase will reduce the overall Sm content in the magnet. The main phase in the final magnet is the RCO5 phase, so the Sm and Co contents in the final magnets in each embodiment are similar; R includes one or more of Sm, Pr, Nd, Gd, and Y.
[0151] The present invention also provides a method for preparing a samarium cobalt permanent magnet, which includes the following steps: first, the above-mentioned samarium cobalt permanent magnet alloy is smelted and cast to obtain a samarium cobalt permanent magnet alloy material; then, it is subjected to hydrogen crushing, air jet milling, pressing and sintering to obtain the desired material.
[0152] The air jet mill sorting includes a first sorting, a second sorting, and a third sorting performed sequentially;
[0153] The powder obtained after the first sorting has a particle size of 2.8μm≤D95≤3.2μm, and the powder with a particle size of 2.8μm≤D95≤3.2μm is removed. The remaining powder after the removal is then sorted a second time.
[0154] The particle size of the powder obtained after the second sorting is 3.3μm≤D10≤4μm and 18μm≤D95≤25μm, and the powder obtained after the second sorting is then subjected to a third sorting.
[0155] The particle size of the powder obtained after the third sorting is 4.1μm≤D10≤5.5μm and 18μm≤D95≤20μm, and the powder obtained after the third sorting is then pressed.
[0156] In this invention, the alloy material for samarium cobalt permanent magnets is preferably the aforementioned alloy material for samarium cobalt permanent magnets.
[0157] In this invention, the smelting conditions are as described above. The casting conditions are as described above.
[0158] In this invention, hydrogen crushing generally includes hydrogen absorption treatment and hydrogen dehydrogenation treatment.
[0159] The temperature of the hydrogen absorption treatment can be 250-300°C, for example, 260°C.
[0160] The pressure of the hydrogen absorption treatment can be 0.1 MPa.
[0161] The temperature of the dehydrogenation treatment can be 550℃~600℃.
[0162] The dehydrogenation treatment time can be 1.5h to 3h, for example 2h.
[0163] In this invention, the O content in the coarse powder obtained after hydrogen crushing is generally less than 100 ppm. The H content in the coarse powder obtained after hydrogen crushing is generally less than 40 ppm.
[0164] In this invention, the air jet mill speed used for the first sorting is preferably 4000-5000 rpm, for example 4500 rpm, 4200 rpm, or 4800 rpm. The particle size of the powder obtained after the first sorting is preferably 2.85 μm ≤ D95 ≤ 3.2 μm, for example 2.9 μm or 3.1 μm.
[0165] In this invention, the air jet mill speed used for the second sorting is preferably 2000–4000 rpm, more preferably 2200–3800 rpm, for example 2500 rpm, 3000 rpm, 3200 rpm, or 3500 rpm. The particle size of the powder obtained after the second sorting is preferably 3.4 μm ≤ D10 ≤ 4 μm, for example 3.5 μm, 3.6 μm, 3.7 μm, or 3.8 μm. The particle size of the powder obtained after the second sorting is preferably 20.1 μm ≤ D95 ≤ 25 μm, for example 21.1 μm, 21.8 μm, 22.5 μm, 24.3 μm, or 24.6 μm.
[0166] In this invention, the air jet mill speed used for the third sorting is preferably 3000-3500 rpm, for example, 3300 rpm, 3100 rpm, or 3400 rpm. The particle size of the powder obtained after the third sorting is preferably 4.2 μm ≤ D10 ≤ 5.5 μm, for example, 4.3 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 5.3 μm, or 5.4 μm. The particle size of the powder obtained after the third sorting is preferably 18.5 μm ≤ D95 ≤ 20 μm, for example, 19.4 μm, 19.2 μm, 19.8 μm, 18.6 μm, 19.5 μm, 19.7 μm, or 18.9 μm.
[0167] In this invention, the air jet milling process includes a conventional air jet milling process. Each air jet milling process has the effect of pulverizing and sorting, but most of the powder pulverization occurs in the first air jet milling process.
[0168] In this invention, the particle size can be determined using a Malvern MS2000 dry and wet laser particle size analyzer.
[0169] In this invention, the magnetic field strength used during pressing is generally 1.0–3.0 T, for example, 2 T. The pressing generally includes orientation pressing and static pressing in sequence. The pressure of the orientation pressing can be 40–60 MPa, for example, 50 MPa. The pressure of the static pressing can be 140–160 MPa, for example, 150 MPa.
[0170] In this invention, the sintering atmosphere can be an inert gas atmosphere. The inert gas can be Ar.
[0171] In this invention, the sintering temperature is preferably 1050–1180°C, for example 1155°C.
[0172] In this invention, the sintering time is preferably 30 to 120 minutes, for example, 90 minutes.
[0173] In this invention, the sintering process preferably further includes an aging treatment.
[0174] The aging treatment temperature is preferably 900–950°C. The aging treatment time is preferably 60–1200 min, for example, 900 min.
[0175] The cooling rate from the sintering temperature to the aging treatment temperature is generally no greater than 2°C / min, for example, 1°C / min.
[0176] Preferably, the aging process also includes a rapid cooling step.
[0177] The rapid cooling rate is greater than 50°C / min and less than 300°C / min, for example, 125°C / min.
[0178] The temperature after rapid cooling can be 400–500°C.
[0179] The present invention also provides an application of samarium cobalt permanent magnets as rotors of permanent magnet motors.
[0180] The inventors of this invention accidentally discovered through creative work that the alloy formulation for samarium-cobalt permanent magnets disclosed in this application can contain a certain proportion of RCO5 and R2CO7 phases in the alloy material. Due to the differences in hardness and hydrogen absorption capacity between the RCO5 and R2CO7 phases during hydrogen fragmentation, the two phases exhibit different fragmentation effects after hydrogen absorption. The R2CO7 phase has low hardness and high hydrogen absorption capacity, resulting in more fracture cracks with smaller crack spacing, higher degree of fragmentation, and finer particle size. Conversely, the RCO5 phase has low hydrogen absorption capacity and high hardness, resulting in fewer cracks, lower degree of fragmentation, and larger particle size. Utilizing the different hydrogen absorption behaviors and hardness characteristics of the two phases, air jet milling can be used to separate and enrich the two phases, thereby producing samarium-cobalt permanent magnets containing a higher proportion of the RCO5 phase, where R includes one or more of Sm, Pr, Nd, Gd, and Y.
[0181] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention.
[0182] The reagents and raw materials used in this invention are all commercially available.
[0183] The positive and progressive effects of this invention are as follows:
[0184] (1) The samarium cobalt permanent magnet of this application has excellent magnetic properties: the remanence of the samarium cobalt permanent magnet of this application is above 9.7 kGs, the maximum magnetic energy product is above 22 MGOe, and the intrinsic coercivity is above 21.5 kOe.
[0185] (2) The samarium cobalt permanent magnet of this application exhibits excellent corrosion resistance: the PCT test weight loss rate of the samarium cobalt permanent magnet is as low as 4.1 mg / cm³. 2 the following. Attached Figure Description
[0186] Figure 1 The image shows the BSE diagram of the samarium-cobalt permanent magnet alloy material of Example 2 after hydrogen degradation.
[0187] Figure 2 The image shows the BSE diagram of the phase structure of the samarium cobalt permanent magnet in Example 2.
[0188] Figure 3 This is a diagram showing the phase differences between the alloy material used for the samarium cobalt permanent magnet in Example 2 and the samarium cobalt permanent magnet itself. Detailed Implementation
[0189] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.
[0190] Example 1
[0191] Step S1, Melting and Casting: Prepare the raw materials according to the formula in Table 1. Melt the samarium-cobalt permanent magnet alloy raw materials under vacuum induction. During the melting process, first evacuate the melting chamber to fully remove air, then fill with argon gas at 80 kPa as a protective gas. The melting temperature is 1580℃, and the melting time is 70 minutes. Centrifugal casting is then used to obtain centrifugal ingots, which are the samarium-cobalt permanent magnet alloy materials.
[0192] Step S2, Hydrogen Decomposition (HD): The samarium cobalt permanent magnet alloy material is placed in the feed tube, and the centrifugal ingot is heated to 260°C under vacuum. After the temperature stabilizes, hydrogen is introduced until the absolute hydrogen pressure reaches 0.1 MPa for hydrogen absorption. After hydrogen absorption, dehydrogenation is carried out at 550°C for 2 hours to obtain coarse powder. The H content in the obtained coarse powder is less than 40 ppm, and the O content is less than 100 ppm.
[0193] Step S3, First sorting (JM1): The coarse powder is pulverized by air jet milling using a QLM-100 fluidized bed mill with a sorting wheel speed of 4500 rpm to obtain fine powder with a particle size D95 of 2.9 μm (the particle size is measured using a Malvern MS2000 dry and wet laser particle size analyzer). This fine powder is removed as waste, and the remaining powder after the waste is removed is used as raw material for the second sorting.
[0194] Step S4, Second Separation (JM2): The powder remaining after removing waste material in step S3 is fed into a fluidized bed air jet mill for further air jet milling. The sorting wheel speed is 3000 rpm, and powder with a particle size D10 of 3.7 μm and D95 of 22.5 μm is obtained, which is used as the raw material for the third separation.
[0195] Step S5, third sorting (JM3): The powder obtained in step S4 is fed into a fluidized bed air jet mill for further air jet milling. The sorting wheel speed is 3300 rpm, and powder with a particle size D10 of 4.8 μm and D95 of 19.4 μm is obtained.
[0196] Step S6, pressing and molding: The powder obtained in step S5 is oriented and pressed under a 2T magnetic field with a pressure of 50MPa to obtain a compact; then, a KJYU150 servo-controlled isostatic press is used for cold isostatic pressing with a pressure of 150MPa to obtain a further densified compact.
[0197] Step S7, sintering and aging: Place the compact in a vacuum sintering furnace and sinter at 1155℃ for 90 min in an argon atmosphere; then slowly cool it to 900℃ at an average cooling rate of 1℃ / min for aging treatment for 900 min; after aging, cool it rapidly, and the time from 900℃ to 400℃ is less than 4 min; thus, the final samarium cobalt permanent magnet material is obtained.
[0198] Examples 2-8 and Comparative Examples 1-7
[0199] The ingredients were prepared according to Table 1, and the preparation process was the same as in Example 1. The difference was that the preparation parameters for each example and comparative example were implemented according to Table 2.
[0200] Table 1. Composition of alloys used in samarium-cobalt permanent magnets
[0201]
[0202]
[0203] Table 2. Three-stage sorting parameters and particle size
[0204]
[0205] Effect Example
[0206] (1) Determination of composition and phase ratio
[0207] The composition of the samarium cobalt permanent magnet alloy materials in Examples 1-8 and Comparative Examples 1-7 was determined using a Panaco Axios max X-ray fluorescence spectrometer (XRF); and the phase ratio was determined using an X-ray diffractometer (X'Pert PRO). The composition and phase ratio of the obtained samarium cobalt permanent magnet alloy materials are shown in Table 3.
[0208] The samarium cobalt permanent magnets in Examples 1-8 and Comparative Examples 1-7 were subjected to the same method described above to determine their composition and phase ratio. The composition and phase ratio of the obtained samarium cobalt permanent magnets are shown in Table 4.
[0209] (2) EPMA (Electron Probe) Test
[0210] The samarium-cobalt permanent magnet alloy material in Example 2 was crushed and observed using the backscattered electron (BSE) imaging function of an EPMA (JXA-8503F (Nippon Electron)) device. Figure 1The samarium cobalt permanent magnet in Example 2 was also observed using BSE, and the results were obtained. Figure 2 ; obtained through XRD testing Figure 3 A comparison diagram of phase differences.
[0211] Depend on Figure 1 It is known that the alloy material used in samarium cobalt permanent magnets contains a certain proportion of SmCo5 phase and Sm2Co7 phase. Due to the different hardness and hydrogen absorption capacity of the SmCo5 phase and the Sm2Co7 phase during the hydrogen fragmentation process, the two phases have different fragmentation effects after hydrogen absorption: Sm2Co7 produces more fragmentation cracks after hydrogen absorption, with smaller crack spacing, higher degree of fragmentation, and finer particle size; SmCo5 produces fewer cracks after hydrogen absorption, with lower degree of fragmentation and larger particle size.
[0212] Depend on Figure 2 It can be seen that the darker gray phase in samarium cobalt permanent magnets is the SmCo5 phase, and the lighter gray phase is the Sm2Co7 phase. Obviously, the proportion of the SmCo5 phase is greater than that of the Sm2Co7 phase. The CoSn2 phase and the Sm2O3 phase are grain boundary phases.
[0213] Depend on Figure 3 This further demonstrates that the proportion of the SmCo5 phase in samarium cobalt permanent magnets is greater than that of the Sm2Co7 phase, while the proportion of the Sm2Co7 phase in the alloy materials used for samarium cobalt permanent magnets is relatively high.
[0214] Table 3 Composition and phase ratio of alloy materials used in samarium cobalt permanent magnets
[0215]
[0216]
[0217] Table 4 Composition and phase ratio of samarium cobalt permanent magnets
[0218]
[0219]
[0220] (3) Magnetic property test
[0221] The results of testing the remanence, maximum energy product, magnetic coercivity (HcB), and intrinsic coercivity (HcJ) of the samarium cobalt permanent magnets in Examples 1-8 and Comparative Examples 1-7 using a PFM14 permanent magnet performance measuring instrument are shown in Table 5.
[0222] As shown in Table 5, the remanence of the samarium cobalt permanent magnets in the embodiments of this application is above 9.7 kGs, the maximum magnetic energy product is above 22 MGOe, and the intrinsic coercivity is above 21.5 kOe.
[0223] The Sm element content in Comparative Example 1 was lower than the range defined in this application, resulting in the formation of Sm2Co in the samarium cobalt permanent magnet. 17 The soft magnetic phase results in lower coercivity.
[0224] In Comparative Example 2, the Sm element content is higher than the range specified in this application. The excessive Sm2Co7 phase in the samarium cobalt permanent magnet results in low remanence and coercivity, as well as poor corrosion resistance.
[0225] In Comparative Example 3, the levels of Fe and M were both higher than those specified in this application. The samarium cobalt permanent magnet had too much non-magnetic phase, poor remanence, and significantly reduced corrosion resistance.
[0226] In Comparative Example 4, the levels of Fe and M were both below the limits specified in this application, making it difficult to achieve densification and sintering, resulting in significantly poorer remanence and corrosion resistance.
[0227] In Comparative Example 5, the particle size of the powder after air jet milling is not within the range specified in this application, making it difficult to obtain a high proportion of SmCo5 phase, resulting in a significant decrease in coercivity and a sharp deterioration in corrosion resistance.
[0228] Comparative Example 6, which only underwent conventional air jet milling, failed to obtain a high proportion of SmCo5 phase, resulting in a significant decrease in coercivity and a sharp deterioration in corrosion resistance.
[0229] Comparative Example 7 only underwent conventional air jet milling without hydrogen crushing, making it difficult to obtain a high proportion of SmCo5 phase, resulting in a significant decrease in coercivity and a sharp deterioration in corrosion resistance.
[0230] (4) Corrosion resistance test
[0231] The samarium cobalt permanent magnets in Examples 1-8 and Comparative Examples 1-7 were tested using a PCT-35 high-pressure accelerated aging tester. The PCT (high-pressure accelerated corrosion test) weight loss test conditions were: vapor pressure 0.2 MPa, relative humidity 100% RH, temperature 120±2℃, and test time 100h. The test results are shown in Table 5.
[0232] As shown in Table 5, the PCT test weight loss rate of the samarium cobalt permanent magnet in this embodiment is as low as 4.1 mg / cm³. 2 The following exhibit excellent corrosion resistance.
[0233] Table 5. Examples of Effects
[0234]
Claims
1. An alloy material for samarium cobalt permanent magnets, characterized in that: In terms of mass percentage, it includes the following components: R: 34.5-38 mas%, wherein R is a rare earth element and includes Sm; Fe: 0.2~1mas%; M: 0.2-1 mas%, wherein M includes one or more of Sn, Al, Cu, Ga and Zn; Co: 60-65mas%; mas% refers to the mass percentage of each element in the alloy material for samarium-cobalt permanent magnets; The alloy material for samarium cobalt permanent magnets comprises RCO5 phase, R2CO7 phase and grain boundary phase. The volume ratio of the RCO5 phase is 55% to 85%, The volume ratio of the R2CO7 phase is 15% to 45%, The volume ratio of the grain boundary phase is 1% to 5%, The sum of the volume ratios of the RCO5 phase, the R2CO7 phase and the grain boundary phase is 100%.
2. The alloy material for samarium-cobalt permanent magnets according to claim 1, characterized in that: The grain boundary phase is a CoSn phase and / or a CoSn2 phase; And / or, the content of R is in the range of 34.54-37.89 mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; And / or, said R further comprises one or more of Pr, Nd, Gd and Y; When the R also includes Pr, the content of Pr is in the range of 0 to 15.5 mas% and is not 0, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; When R also includes Y, the content of Y is in the range of 0 to 18 mas% and is not 0, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; And / or, the content of Sm is in the range of 15mas% to 38mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium-cobalt permanent magnets; And / or, the Fe content ranges from 0.21mas% to 1mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium-cobalt permanent magnets; And / or, the content of M is in the range of 0.5-1mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; And / or, the M includes one or more of Sn, Al and Cu; When the M includes Sn, the content of Sn is in the range of 0.3-1mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium-cobalt permanent magnets; When the M includes Al, the content of Al is in the range of 0.1 to 0.5 mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; When the M includes Cu, the content of Cu is in the range of 0.1 to 0.5 mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; And / or, the content of Co is in the range of 60-64.5mas%mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; Alternatively, the samarium cobalt permanent magnet alloy material is composed of the following components in percentage by mass: Sm, 15-38mas%; Co, 60-64.5mas%; Fe, 0.3-1mas%; Sn, 0.3-1mas%; RCO5 phase 55%-85%, R2Co7 phase 15%-45%, grain boundary phase 1%-5%; Alternatively, the samarium cobalt permanent magnet alloy material is composed of the following components in percentage by mass: Sm, 15-38mas%; Co, 60-64.5mas%; Fe, 0.3-1mas%; Sn, 0.3-1mas%, Al, 0.1-0.5mas%; RCO5 phase 55%-85%, R2Co7 phase 15%-45%, grain boundary phase 1%-5%; Alternatively, the samarium cobalt permanent magnet alloy material is composed of the following components in percentage by mass: Sm, 15~38mas%; Co, 60~64.5mas%; Fe, 0.3~1mas%; Sn, 0.3~1mas%, Al, 0.1~0.5mas%, Cu0.1~0.5mas%; RCO5 phase 55%~85%, R2Co7 phase 15%~45%, grain boundary phase 1%~5%.
3. The alloy material for samarium-cobalt permanent magnets according to claim 2, characterized in that: The content range of R is 35.05mas%, 36.53mas%, 37.48mas%, 35.57mas%, 36.11mas% or 35.13mas%, mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnet; And / or, the R also includes Pr and / or Y; wherein the RCO5 phase also includes a YCo5 phase and / or a PrCO5 phase; the R2CO7 phase also includes a Y2Co7 phase and / or a Pr2CO7 phase; And / or, when the R also includes Pr, the content of Pr is in the range of 5.04mas% or 15.01mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; And / or, when R also includes Y, the content of Y is in the range of 4.97mas% or 17.96mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; And / or, the content of Sm is in the range of 34.54mas%, 35.05mas%, 36.53mas%, 37.48mas%, 37.89mas%, 20.56mas%, 18.15mas%, or 25.12mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; And / or, the content of Fe is in the range of 0.61mas%, 0.62mas%, 0.53mas%, 0.32mas%, 0.95mas%, 0.77mas% or 0.64mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; And / or, the content range of M is 0.55mas% or 0.6mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; And / or, when the M includes Sn, the content of Sn is in the range of 0.31mas%, 0.58mas%, 0.44mas%, 0.32mas%, 0.51mas%, 0.62mas%, 0.54mas% or 0.64mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; And / or, when the M includes Al, the content of Al is in the range of 0.12mas% or 0.32mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; And / or, when the M includes Cu, the content of Cu is in the range of 0.15mas%, 0.11mas% or 0.13mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; And / or, the content of Co is in the range of 64.22mas%, 63.75mas%, 62.27mas%, 61.63mas%, 61.28mas%, 62.86mas%, 62.48mas% or 63.59mas%, where mas% refers to the mass percentage of each element in the alloy material for samarium cobalt permanent magnets; Alternatively, the samarium cobalt permanent magnet alloy material is composed of the following components in percentage by mass: Sm, 35.05mas%; Co, 63.75mas%; Fe, 0.62mas%; Sn, 0.58mas%, SmCo5 phase 72.5%, Sm2Co7 phase 24.5%, grain boundary phase 3%; Alternatively, the samarium cobalt permanent magnet alloy material is composed of the following components in percentage by mass: Sm, 34.54mas%; Co, 64.22mas%; Fe, 0.61mas%; Sn, 0.31mas%, Al, 0.32mas%, SmCo5 phase 78.8%, Sm2Co7 phase 18.1%, grain boundary phase 3.1%; Alternatively, the alloy material for samarium cobalt permanent magnets is composed of the following components in mass percentage: Sm, 36.53mas%; Co, 62.27mas%; Fe, 0.53mas%; Sn, 0.44mas%, Al, 0.12mas%, Cu0.11mas%, SmCo5 phase 64.7%, Sm2Co7 phase 32.5%, grain boundary phase 2.8%; Alternatively, the alloy material for samarium cobalt permanent magnets is composed of the following components in mass percentage: Sm, 37.48mas%; Co, 61.63mas%; Fe, 0.32mas%; Sn, 0.32mas%, Al, 0.1mas%, Cu 0.15mas%, RCO5 phase 60.2%, R2Co7 phase 37.8%, grain boundary phase 2%; Alternatively, the samarium cobalt permanent magnet alloy material is composed of the following components in percentage by mass: Sm, 37.89mas%; Co, 61.28mas%; Fe, 0.21mas%; Sn, 0.49mas%, Cu 0.13mas%, Sm2Co7 phase 56.3%, Sm2Co7 phase 42%, grain boundary phase 1.7%; Alternatively, the samarium cobalt permanent magnet alloy material is composed of the following components in percentage by mass: Sm, 20.56mas%; Pr, 15.01mas%; Co, 62.86mas%; Fe, 0.95mas%; Sn, 0.62mas%, SmCo5 phase and PrCO5 phase 71.1%, Sm2Co7 phase and Pr2CO7 phase 24.8%, grain boundary phase 4.1%; Alternatively, the samarium cobalt permanent magnet alloy material is composed of the following components in percentage by mass: Sm, 18.15mas%; Y, 17.96mas%; Co, 62.48mas%; Fe, 0.77mas%; Sn, 0.54mas%; Al 0.1mas%, SmCo5 phase and YCo5 phase 68.4%, Sm2Co7 phase and Y2Co7 phase 28%, grain boundary phase 3.6%; Alternatively, the samarium cobalt permanent magnet alloy material is composed of the following components in percentage by mass: Sm, 25.12mas%; Pr5.04mas%; Y, 4.97mas%; Co, 63.59mas%; Fe, 0.64mas%; Sn, 0.64mas%, SmCo5 phase, PrCO5 phase and YCo5 phase 70.8%, Sm2Co7 phase, Pr2CO7 phase and Y2Co7 phase 26%, grain boundary phase 3.2%.
4. A method for preparing the alloy material for samarium-cobalt permanent magnets according to any one of claims 1 to 3, characterized in that: It includes the following steps: The samarium cobalt permanent magnet alloy is melted and cast; the melting time is 1 to 5 hours; The smelting temperature is 1480-1580°C; The pressure during the smelting process is 50-80 kPa; the casting method is a belt casting method, a centrifugal casting method or a BOOKMOLD type casting method.
Citation Information
Patent Citations
SmCo5 type samarium-cobalt permanent magnet material and preparation method and application thereof
CN113517126A